Principal's Experience in Internalizing Handep Values Based on the Huma Betang Philosophy: Phenomenological Studies at Elementary School Number 2 Palangka Raya - Melinda Prawati; Carolina Fransiska; Widya Permata Dilla; Simpun Simpun; Kristiani Natalia; Laila Rahmawati; Femmy Femmy; Maneka Ciciana (IKIP PGRI Bojonegoro, 2026)
This research aims to explore the principal's subjective experience in internalizing Handep values which include harmony, adaptation, reason, dedication, efficiency and unity based on the Huma Betang philosophy of the Dayak people in Central Kalimantan, Indonesia. The philosophy of Huma Betang, as a symbol of longhouses symbolizing communal living, mutual assistance and social balance. Using an interpretive phenomenology approach, this research was carried out at SD Negeri 2 Palangka. Data were collected through semi-structural in-depth interviews recorded and transcribed, supplemented by participant observation in the school environment. Data analysis was carried out thematically with source triangulation to ensure validity. The findings reveal that the experience of internalizing Handep not only enriches leadership identity, but also creates an inclusive school climate. Recommendations include the integration of the Huma Betang philosophy in the national leadership curriculum to support continuing education.